2022
DOI: 10.1002/pon.5897
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of testing human papillomavirus positive in Australia's human papillomavirus‐based cervical screening program: A cross‐sectional survey

Abstract: Objective To examine the impact of self‐reported human papillomavirus (HPV) test result (HPV negative, HPV positive, HPV result unknown) on a range of psychosocial outcomes. Methods Women and other people with a cervix in Australia aged 25–74 years who reported having participated in cervical screening since December 2017 were recruited through Facebook and Instagram to complete an online survey. The primary outcome measures were anxiety, emotional distress, and general distress. Results Nine hundred fifteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The participants involved in the research had an abnormal cytology result or had received an HPV-positive test result. In order to understand the impact of an abnormal cytology result, HPV infection, and subsequent medical interventions on women’s mental health and sexual life, participants were screened and examined according to Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria, using the Hospital Anxiety and Depression Scale (HADS) [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], Beck Depression Inventory (BDI) [ 29 , 30 ], Beck Anxiety Inventory (BAI) [ 29 , 30 , 31 ], Symptom Checklist-Revised (SCL-90) [ 32 ], Psychosocial Effects of Abnormal Pap Smears Questionnaire short-form (PEAPS-Q) [ 11 , 24 , 33 , 34 , 35 ], State-Trait Anxiety Inventory (STAI) [ 6 , 7 , 8 , 9 , 10 , 11 , 16 , 33 , 35 , 36 , 37 , 38 , 39 , 40 ], Female Sexual Function Index (FSFI) [ 15 , 17 , 31 , 39 , 41 , 42 ], HPV Impact Profile (HIP) [ 7 , 9 , 21 , 25 <...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants involved in the research had an abnormal cytology result or had received an HPV-positive test result. In order to understand the impact of an abnormal cytology result, HPV infection, and subsequent medical interventions on women’s mental health and sexual life, participants were screened and examined according to Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria, using the Hospital Anxiety and Depression Scale (HADS) [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], Beck Depression Inventory (BDI) [ 29 , 30 ], Beck Anxiety Inventory (BAI) [ 29 , 30 , 31 ], Symptom Checklist-Revised (SCL-90) [ 32 ], Psychosocial Effects of Abnormal Pap Smears Questionnaire short-form (PEAPS-Q) [ 11 , 24 , 33 , 34 , 35 ], State-Trait Anxiety Inventory (STAI) [ 6 , 7 , 8 , 9 , 10 , 11 , 16 , 33 , 35 , 36 , 37 , 38 , 39 , 40 ], Female Sexual Function Index (FSFI) [ 15 , 17 , 31 , 39 , 41 , 42 ], HPV Impact Profile (HIP) [ 7 , 9 , 21 , 25 <...…”
Section: Resultsmentioning
confidence: 99%
“…The observational studies were classified using the ROBINS-E tool. Fourteen of the fifty-six included studies were rated as ‘low risk of bias’ [ 10 , 13 , 15 , 22 , 24 , 25 , 26 , 29 , 30 , 34 , 36 , 40 , 47 , 48 ], sixteen as ‘some concerns’ [ 8 , 9 , 11 , 14 , 17 , 19 , 32 , 39 , 44 , 49 , 52 , 53 , 54 , 55 , 56 , 67 ], twenty as ‘high risk’ [ 6 , 7 , 16 , 27 , 31 , 33 , 35 , 38 , 41 , 42 , 43 , 45 , 46 , 50 , 51 , 57 , 58 , 59 , 60 , 61 ], and five as ‘very high risk’ [ 62 , 63 , 64 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no psychological difference between those who detected polyps and those who received negative results ( 35 , 36 ). (d) Cervical cancer: Several studies have shown that an abnormal diagnosis of cervical cancer caused negative emotions, such as increased anxiety levels ( 16 , 37 ). (e) Gastrointestinal cancer: A prior study in Iran found that informing the results of screening may lead to a psychological burden for screeners ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the psychological impact of cancer screening are inconsistent. Current research in this field mainly focuses on the following types of cancer: lung cancer, breast cancer, colorectal cancer, cervical cancer and ovarian cancer ( 7 , 16 18 ). However, research on the psychological impact caused by EC screening is still limited and unclear.…”
Section: Introductionmentioning
confidence: 99%